Mycoplasma feriruminatoris sp. nov., a fast growing Mycoplasma species isolated from wild Caprinae - Jores, Joerg; Fischer, A.; Sirand-Pugnet, P.; Thomann, A.; Liebler-Tenorio, E.M.; Schnee, C.; Santana-Cruz, I.; Heller, M.; Frey, J. (Elsevier, 2013)
Five Mycoplasma strains from wild Caprinae were analyzed: four from Alpine ibex (Capra ibex) which died at the Berlin Zoo between 1993 and 1994, one from a Rocky Mountain goat collected in the USA prior to 1987. These five strains represented a population different from the populations belonging to the ‘Mycoplasma mycoides cluster’ as tested using multi locus sequence typing, Matrix-assisted laser desorption/ionization time of flight mass spectrometry analysis and DNA–DNA hybridization. Analysis of the 16S rRNA gene (rrs), genomic sequence based in silico as well as laboratory DNA–DNA hybridization, and the analysis of phenotypic traits in particular their exceptionally rapid growth all confirmed that they do not belong to any Mycoplasma species described to date. We therefore suggest these strains represent a novel species, for which we propose the name Mycoplasma feriruminatoris sp. nov. The type strain is G5847T (= DSM 26019T = NCTC 1362T).